Pengaturan Pembatasan Jumlah Pembuatan Akta Notaris dalam Perspektif Peraturan Jabatan Notaris - Mutya Pratiwi; Fauzi Syam; Syamyir Syamyir (Wajah Hukum, 2022)
There is no regulation limiting the number of deeds made by a Notary in the perspective of the notary position regulation. What is the authority of the Central Honorary Council in imposing sanctions on a notary who issues a deed that exceeds the normal limit. This study uses a normative juridical method. The results of this study are that the making of a Notary deed is regulated in the provisions of Article 38 of the UUJN, and the provisions of making 20 (twenty) deeds per day according to the Regulation of the Honorary Council of the Indonesian Notary Association Number 1 of 2017 in ensuring the certainty of the date and time determined by the provisions The Law on Notary Positions is in compliance. If the notary violates this DKP regulation No. 1 of 2017 concerning the reasonable limit for making a notary deed per day, besides being subject to ethical sanctions for violating KEN regulations, notaries can also be subject to administrative sanctions for not complying with UUJN orders. Notaries who commit such violations can be the object of summons and examination from the Regional Honorary Council according to their level of authority, DKD has the right to summon and examine notaries who are indicated to have committed violations either based on reports or direct findings, DKD is also authorized to give direct sanctions or provide results of examinations to be carried out further examination to the Regional Honorary Council.